Sleep quality and emotional reactivity in patients with borderline personality disorder - Socci, Valentina; Festucci, Fabiana; Barlattani, Tommaso; Salfi, Federico; D'Aurizio, Giulia; Rossi, Rodolfo; Ferrara, Michele; Rossi, Alessandro; Pacitti, Francesca; Tempesta, Daniela (Frontiers in Sleep, 2024)
Background/objective: Emotional dysregulation is bidirectionally associated with sleep disturbances, with potential critical implications for emotional reactivity in borderline personality disorder (BPD). This study evaluated subjective and objective sleep quality, emotional regulation and emotional reactivity in 20 patients with BPD compared to 20 non-clinical individuals.Methods: Subjective and objective sleep quality was assessed using the Pittsburgh Sleep Quality Index (PSQI) and a 3-day actigraphic measurement. Emotional regulation was evaluated using the Difficulties in Emotion Regulation Scale (DERS) and the Berkeley Expressivity Questionnaire (BEQ). Further, each participant underwent an emotional reactivity task selected from the International Affective Picture System (IAPS).Results: Compared to control subjects, individuals with BPD reported poor subjective sleep quality and objective sleep continuity disturbances with more sleep fragmentation and decreased sleep efficiency. Moreover, BPD patients showed emotional dysregulation and altered subjective reactivity to emotional stimuli, particularly positively-valenced stimuli.These results suggest the importance of further clarifying the specific direction of sleepdependent emotional modulation in individuals with BPD, with significant clinical implications for patients with co-occurring sleep disturbances.